From Fear to Hope: Psychological Well-being Victims of Domestic Violence - Muhammad Nurul Yulianto; Fx. Wahyu Widiantoro (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Domestic Violence (DV) is a complex phenomenon that not only inflicts physical harm but also leaves deep psychological scars on victims. Data from the Indonesian National Commission on Violence Against Women (Komnas Perempuan) in 2023 indicates a significant increase in DV cases, particularly against women, often affecting their quality of life and psychological well-being. This study aims to explore the subjective experiences of DV survivors regarding their psychological well-being. Using a qualitative phenomenological approach, the study involved three adult women who had experienced DV, with data collected through in-depth interviews and observations. Data analysis employed an interpretative phenomenological method to uncover the deeper meanings of the victims’ lived experiences. The findings reveal that DV negatively impacts the six dimensions of psychological well-being identified by Ryff: self-acceptance, positive relations with others, autonomy, environmental mastery, purpose in life, and personal growth. The implications of this study highlight the necessity of a holistic intervention that not only focuses on victims’ psychological recovery but also strengthens social support systems, provides adequate protection, and empowers survivors to rebuild their identity, independence, and overall quality of life.Kekerasan Dalam Rumah Tangga (KDRT) merupakan fenomena kompleks yang tidak hanya menimbulkan luka fisik, tetapi juga meninggalkan dampak psikologis mendalam bagi korban. Data Komnas Perempuan tahun 2023 menunjukkan peningkatan signifikan kasus KDRT, khususnya terhadap perempuan, yang sering kali memengaruhi kualitas hidup dan kesejahteraan psikologis mereka. Penelitian ini bertujuan mengeksplorasi pengalaman subjektif korban KDRT terkait kondisi kesejahteraan psikologis mereka. Menggunakan pendekatan kualitatif fenomenologis, penelitian melibatkan tiga perempuan dewasa yang pernah mengalami KDRT, dengan metode pengumpulan data melalui wawancara mendalam dan observasi. Analisis data dilakukan menggunakan metode fenomenologi interpretatif untuk mengungkap makna mendalam dari pengalaman korban. Hasil penelitian menunjukkan bahwa KDRT berdampak negatif pada enam dimensi kesejahteraan psikologis menurut Ryff, meliputi penerimaan diri, hubungan positif dengan orang lain, otonomi, penguasaan lingkungan, tujuan hidup, dan pertumbuhan pribadi. Implikasi dari temuan ini menunjukkan perlunya intervensi holistik yang tidak hanya berfokus pada pemulihan psikologis korban, tetapi juga pada penguatan sistem dukungan sosial, penyediaan perlindungan yang memadai, serta pemberdayaan korban agar mampu membangun kembali identitas, kemandirian, dan kualitas hidup mereka.